Empowering the Tri Hita Karana Paradigm for the Community: As an Effort to Prevent and Combat Environmental Crime - Saefudin, Yusuf; Rakhmatullah, Bha'iq Roza; Mohd Hassan, Fareed; Ma'ruf, Ma'ruf; Kurnianingsih, I Desak Ketut Dewi Satiawati (Journal of Law, Environmental and Justice, 2025)
This article explores the integration of Tri Hita Karana, a Balinese philosophical framework emphasizing harmony among humans, nature, and the divine, as a paradigm of community empowerment in addressing environmental crimes. Environmental crimes, such as illegal logging, pollution, and land degradation, not only threaten ecological sustainability but also undermine social justice and cultural values. Conventional law enforcement often encounters limitations in ensuring compliance and fostering ecological justice, especially when community participation is weak. This study argues that Tri Hita Karana can function as a cultural-legal tool to strengthen collective awareness, enhance preventive measures, and support restorative approaches in environmental law enforcement. By adopting normative legal research and conceptual analysis, the article highlights how the principles of Tri Hita Karana can be integrated into legal frameworks and community-based practices, thereby reinforcing environmental governance. Ultimately, the integration of Tri Hita Karana promotes ecological justice by balancing punitive measures with values of harmony, sustainability, and community empowerment. The findings indicate that incorporating Tri Hita Karana values into environmental law enforcement enhances community participation, encourages environmentally responsible behavior, and provides a restorative dimension to legal practices. This integration not only contributes to more effective prevention and mitigation of environmental crimes but also reinforces the pursuit of ecological justice